Pengembangan Aplikasi Maranatha E-signature - Bernard Renaldy Suteja; Mewati Ayub; Kafka Febianto Agiharta (Maranatha University Press, 2023)
Using digital signature in a document, especially in work from home situation, becomes crucial to misuse. The digital signature is a schema to identify somebody uniquely and to prove the originality of a document. The development of information technology allows digital signatures as a tool to ensure the originality of information. The aim of the study is to develop an application that uses Quick Response (QR) Code as a digital signature. So QR Code can work as a tool to authenticate the leader’s signature or document verification. After the application was built and applied, users’ evaluation was performed through questionnaires. The result shows that 44% of users state that the application has been well used and beneficial. There are some suggestions for application revision from 34% of users, whereas 22% have no comment.